2012
DOI: 10.1021/ja308969p
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Functionalization Degree of Single-Walled Carbon Nanotubes Having Various Substituents

Abstract: Introducing substituents onto SWNT sidewalls increases their solubility and tunes their properties. Controlling the degree of functionalization is important because the addition of numerous functional groups on the sidewall degrades their intrinsic useful electronic properties. We examined the synthesis and characterization of sidewall-functionalized SWNTs in this study. The functionalized SWNTs ((1)R-SWNTs-(2)R) were prepared in a one-pot reaction of SWNTs with alkyllithium ((1)RLi) followed by alkyl bromide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 43 publications
4
35
0
Order By: Relevance
“…In contrast, the R value of the F-SWCNTs was 0.923 ± 0.042; further, the peak related to the radial breathing mode (RBM) could not be detected. It has been reported that an increase in the intensity of the D-band occurs not only owing to an increase in the number of topological defects in CNTs [23] but also owing to an increase in the number of sp 3 -hybridized covalent bonds formed by the CNTs [55][56][57][58]. In this study, the fact that the observed R value was high indicated that all the fluorine groups associated with the CF 0.39 stoichiometry were introduced to the nanotubes and that they bonded with the C tube atoms of the nanotube frame through sp 3 -hybridized covalent bonds.…”
Section: Samplesmentioning
confidence: 99%
“…In contrast, the R value of the F-SWCNTs was 0.923 ± 0.042; further, the peak related to the radial breathing mode (RBM) could not be detected. It has been reported that an increase in the intensity of the D-band occurs not only owing to an increase in the number of topological defects in CNTs [23] but also owing to an increase in the number of sp 3 -hybridized covalent bonds formed by the CNTs [55][56][57][58]. In this study, the fact that the observed R value was high indicated that all the fluorine groups associated with the CF 0.39 stoichiometry were introduced to the nanotubes and that they bonded with the C tube atoms of the nanotube frame through sp 3 -hybridized covalent bonds.…”
Section: Samplesmentioning
confidence: 99%
“…[16] Meanwhile, we have previously reported that the substituents on SWNTs, and their bulkiness, strongly affect the degree of functionalization during the reductive alkylation of SWNTs. [20,21] Thus, we envisage the reductive alkylation with the appropriate choice of substituents, can be used to control the PL properties of SWNTs. Herein, we report the PL properties of dialkylated SWNTs with varying degrees of functionalization.…”
mentioning
confidence: 99%
“…Dialkylated SWNTs (R 1 -SWNTs-R 2 ) were synthesized using butyllithium (R 1 Li) and butyl bromide (R 2 Br) according to previously reported methods. [20,21] (Scheme 1) In nBu-SWNTs-R (R = nBu, isoBu, secBu, and tBu) and tBu-SWNTs-R (R = nBu, isoBu, and secBu), the characteristic E 11 and E 22 absorption peaks were mostly diminished by the alkylation, indicating sidewall functionalization proceeded effectively. On the other hand, the absorption spectrum of tBu-SWNTs-tBu exhibited relatively small changes, as shown in Fig.…”
mentioning
confidence: 99%
“…We decided to exploit the two‐step nucleophilic addition of organolithium compounds and electrophile capture grafting . This method has already been used for the trapping of different electrophiles, either alkanes for dispersion purposes or other dead‐end moieties . We, hereby, propose the use of a new, easily accessible, cheap, and atom‐efficient electrophile: propargyl bromide (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Such bundles affect their solubility in most organic solvents and water.T herefore, the race forn ew functionalization protocols featuring high loading, reproducibility,r obustness, andh omogeneityo ff unctions is still on, especially in the case of graphene.W ed ecided to exploit the two-step nucleophilic addition of organolithium compounds and electrophile capture grafting. [12][13][14] This methodh as already been used for the trapping of different electrophiles, either alkanes for dispersion purposes [15,16] or other dead-endm oieties. [14,[17][18][19][20][21] We, hereby, propose the use of an ew,e asily accessible, cheap,a nd atomefficient electrophile:p ropargyl bromide (Scheme1).…”
mentioning
confidence: 99%